1998
DOI: 10.1183/09031936.98.12010113
|View full text |Cite
|
Sign up to set email alerts
|

Aetiology and outcome of severe community-acquired pneumonia in Singapore

Abstract: The aim of this study was to determine the aetiology and outcome of severe community-acquired pneumonia, and to assess whether the existing guidelines for initial antimicrobial therapy are being applied. The records of 57 consecutive nonimmunocompromised patients admitted to the medical intensive care unit (ICU) between January 1989 and May 1993 with this diagnosis were reviewed. The microbiological data, chest radiographic changes and outcome were analysed. Nine (16%) of the 57 patients had pulmonary tubercul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
2
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 12 publications
1
38
2
1
Order By: Relevance
“…This was higher than the overall mortality recently reported (7)(8)(9)(10)(11)(14)(15)(16)(17)(18), and only two previous reports had a higher rate than that of this study with regard to overall mortality (12,13). Such discrepancies may be explained by varying degrees of the criteria requiring ICU admittance, the severity of illness, underlying medical conditions, and deaths unrelated to pneumonia.…”
Section: Discussioncontrasting
confidence: 88%
See 2 more Smart Citations
“…This was higher than the overall mortality recently reported (7)(8)(9)(10)(11)(14)(15)(16)(17)(18), and only two previous reports had a higher rate than that of this study with regard to overall mortality (12,13). Such discrepancies may be explained by varying degrees of the criteria requiring ICU admittance, the severity of illness, underlying medical conditions, and deaths unrelated to pneumonia.…”
Section: Discussioncontrasting
confidence: 88%
“…Therefore gramnegative rods might have been detected at higher rates than usual. Although M. tuberculosis was isolated in 2 patients (2.8%), the prevalence of tuberculosis is still high in Asian countries (13).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Aetiological pathogens associated with community-acquired pneumonia 3.3.1. Major community-acquired pneumonia bacterial pathogens Table 2 lists major aetiological pathogens associated with CAP amongst adults in the Asia-Pacific region [14,15,[24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42]. The multinational Asian Network for Surveillance of Resistant Pathogens (ANSORP) recently reported that Streptococcus pneumoniae accounted for 29.2% of isolates from adults with CAP in South Korea, China, Taiwan, Hong Kong, India, Singapore, Vietnam and the Philippines [43].…”
Section: Risk Factors For Community-acquired Pneumoniamentioning
confidence: 99%
“…In a retrospective study from Singapore [15] looking at the aetiology of severe CAP in non-immunocompromised patients, there was a surprisingly high incidence of M. tuberculosis in the study population (9 of 57 patients).…”
Section: Case Reportmentioning
confidence: 99%